Cost-effectiveness of psychosocial assessment for individuals who present to hospital following self-harm in England: A model-based retrospective analysis. Issue 1 (31st January 2022) - McDaid, David; Park, A-La; Tsiachristas, Apostolos; Brand, Fiona; Casey, Deborah; Clements, Caroline; Geulayov, Galit; Kapur, Nav; Ness, Jennifer; Waters, Keith; Hawton, Keith
Abstract: Background: Guidance in England recommends psychosocial assessment when presenting to hospital following self-harm but adherence is variable. There is some evidence suggesting that psychosocial assessment is associated with lower risk of subsequent presentation to hospital for self-harm, but the potential cost-effectiveness of psychosocial assessment for hospital-presenting self-harm is unknown. Methods: A three-state four-cycle Markov model was used to assess cost-effectiveness of psychosocial assessment after self-harm compared with no assessment over 2 years. Data on risk of subsequent self-harm and hospital costs of treating self-harm were drawn from the Multicentre Study of Self-Harm in England, while estimates of effectiveness of psychosocial assessment on risk of self-harm, quality of life, and other costs were drawn from literature. Incremental cost-effectiveness ratios (ICERs) for cost per Quality Adjusted Life Year (QALY) gained were estimated. Parameter uncertainty was addressed in univariate and probabilistic sensitivity analyses. Results: Cost per QALY gained from psychosocial assessment was £10, 962 (95% uncertainty interval [UI] £15, 538–£9, 219) from the National Health Service (NHS) perspective and £9, 980 (95% UI £14, 538–£6, 938) from the societal perspective. Results were generally robust to changes in model assumptions. The probability of the ICER being below £20, 000 per QALY gained was 78%, rising to 91% with a £30, 000 threshold. Conclusions: Psychosocial assessment as implemented in the English NHS is likely to be cost-effective. This evidence could support adherence to NICE guidelines. However, further evidence is needed about the precise impacts of psychosocial assessment on self-harm repetition and costs to individuals and their families beyond immediate hospital stay.